1999
DOI: 10.1007/s004310051154
|View full text |Cite
|
Sign up to set email alerts
|

Soluble vascular cell-adhesion molecule-1 and soluble intercellular adhesion molecule-1 correlate with lipid and apolipoprotein risk factors for coronary artery disease in children

Abstract: Our data indicate that intervention to normalize risk factors for coronary artery disease should be started at a young age to prevent increased expression of cell adhesion molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 43 publications
5
7
0
1
Order By: Relevance
“…16 A negative correlation between the age of young patients and the concentrations in adhesion molecules supports the findings of Ohta et al, who first described the clinical usefulness of assessing adhesion molecules as a marker of the first phase of atherosclerosis in children. 17 Our study confirmed the endothelial activation in obese children and the negative correlation between the age of children and the concentrations of sE.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 A negative correlation between the age of young patients and the concentrations in adhesion molecules supports the findings of Ohta et al, who first described the clinical usefulness of assessing adhesion molecules as a marker of the first phase of atherosclerosis in children. 17 Our study confirmed the endothelial activation in obese children and the negative correlation between the age of children and the concentrations of sE.…”
Section: Discussionsupporting
confidence: 90%
“…[16][17][18][19][20] showed that the concentrations of sICAM-1 and sVCAM-1 were significantly greater in children than in adults, and these concentra- tions were found to decline with age. 16 A negative correlation between the age of young patients and the concentrations in adhesion molecules supports the findings of Ohta et al, who first described the clinical usefulness of assessing adhesion molecules as a marker of the first phase of atherosclerosis in children.…”
Section: Discussionmentioning
confidence: 93%
“…These findings are in part and not entirely consistent with recently provided evidence by Ohta et al (26) in a childhood Japanese population. In that study an association of sVCAM-1 and sICAM-1 and serum lipid profile was identified whereas sE-selectin values were not determined and sP-selectin levels did not correlate with any lipid fraction.…”
Section: Discussionsupporting
confidence: 68%
“…Ohta, Saku, Takata et al 1999, Rohde et al 1999) others do not (Hwang et al 1997, Saku, Zhang, Ohta et al 1999) may be attributable to the small sample sizes and the selection biases of clinically based studies, in which`control' subjects are available due to their need for diagnostic services (e.g. echocardiography) .…”
Section: Discussionmentioning
confidence: 96%